Bipolar plate, cell frame, cell stack, and redox flow battery
The bipolar plate for redox flow batteries, featuring a laminated structure of composite sheets with conductive and resin-filled voids, addresses the need for enhanced mechanical strength and conductivity, improving the performance and reliability of the batteries.
Patent Information
- Application Number
- JP2023550856
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-09-29
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2041-09-29
AI Technical Summary
Redox flow batteries require bipolar plates with excellent mechanical strength to withstand bending stresses during handling and manufacturing, while also maintaining electrical conductivity and liquid shielding properties.
The bipolar plate is composed of multiple composite sheets laminated together with a first mixture, where each composite sheet includes a resin sheet with voids filled with a second mixture containing conductive particles and a resin binder, enhancing mechanical strength and conductivity.
The laminated structure of the bipolar plate provides superior mechanical strength, resistance to bending, and improved liquid shielding properties, while maintaining high electrical conductivity, thus enhancing the productivity and reliability of redox flow batteries.
Smart Images

Figure 0007665767000002 
Figure 0007665767000003 
Figure 0007665767000004
Abstract
Description
[Technical Field]
[0001] The present disclosure relates to a bipolar plate, a cell frame, a cell stack, and a redox flow battery. [Background technology]
[0002] Generally, a redox flow battery includes a cell stack in which multiple battery cells are stacked. Each battery cell includes a positive electrode, a negative electrode, and a membrane disposed between the positive and negative electrodes. The cell stack includes bipolar plates that separate adjacent battery cells.
[0003] Patent Document 1 discloses a bipolar plate on which carbon felt is laminated. This bipolar plate is a laminate in which carbon felt is laminated in the surface direction of the bipolar plate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Japanese Patent Application Publication No. 11-162496 Summary of the Invention
[0005] The bipolar plate of the present disclosure is a bipolar plate used in a redox flow battery, and includes a plurality of composite sheets and a first mixture that bonds the stacked composite sheets together, each of the plurality of composite sheets including a resin sheet that includes a plurality of voids and a second mixture that fills at least a portion of the plurality of voids in the resin sheet, and each of the first mixture and the second mixture includes a plurality of conductive particles and a resin binder that fixes the plurality of conductive particles to the resin sheet.
[0006] The cell frame of the present disclosure comprises the bipolar plate of the present disclosure.
[0007] The cell stack of the present disclosure includes the cell frame of the present disclosure.
[0008] The redox flow battery of the present disclosure comprises the cell stack of the present disclosure. [Brief explanation of the drawings]
[0009] [Figure 1] FIG. 1 is a schematic diagram showing the configuration of a redox flow battery according to an embodiment. [Figure 2] FIG. 2 is a schematic diagram showing the configuration of a cell stack provided in a redox flow battery. [Figure 3] FIG. 3 is a schematic perspective view showing a bipolar plate according to the embodiment. [Figure 4] FIG. 4 is a schematic cross-sectional view showing an enlarged cross section of a bipolar plate according to an embodiment. [Figure 5] FIG. 5 is a schematic cross-sectional view showing the configuration of a composite sheet in a bipolar plate according to an embodiment. [Figure 6] FIG. 6 is an enlarged schematic view showing the vicinity of the boundary between composite sheets in a bipolar plate according to an embodiment. [Figure 7] FIG. 7 is a schematic cross-sectional view showing an enlarged cross section of a bipolar plate according to a modified example. [Figure 8] FIG. 8 is a schematic cross-sectional view showing the configuration of a composite sheet in a bipolar plate according to a modified example. [Figure 9] FIG. 9 is an enlarged schematic view showing the vicinity of the boundary between composite sheets in a bipolar plate according to a modified example. [Figure 10] FIG. 10 is an enlarged schematic view showing the vicinity of a surface portion of a bipolar plate according to a modified example. DETAILED DESCRIPTION OF THE INVENTION
[0010] [Problem to be solved by this disclosure] In redox flow batteries, bipolar plates with excellent mechanical strength are desired.
[0011] The main role of bipolar plates used in redox flow batteries is to electrically connect the positive and negative electrodes of adjacent battery cells and to prevent mixing of electrolytes between adjacent battery cells. Therefore, bipolar plates must be electrically conductive and impermeable to electrolytes. Furthermore, bipolar plates may be subjected to bending stress during handling, for example, during cell frame manufacturing. This bending stress can cause the bipolar plates to crack. Therefore, from the perspective of productivity of parts that use bipolar plates, bipolar plates are required to have high mechanical strength that can withstand bending stress during handling. Until now, there has been little research into improving the mechanical strength of bipolar plates.
[0012] An object of the present disclosure is to provide a bipolar plate having excellent mechanical strength. Another object of the present disclosure is to provide a cell frame including the bipolar plate, a cell stack including the cell frame, and a redox flow battery including the cell stack.
[0013] [Effects of this disclosure] The bipolar plate of the present disclosure has excellent mechanical strength. The cell frame of the present disclosure, the cell stack of the present disclosure, and the redox flow battery of the present disclosure include a bipolar plate with excellent mechanical strength.
[0014] [Description of the embodiments of the present disclosure] First, embodiments of the present disclosure will be listed and described.
[0015] (1) A bipolar plate according to an embodiment of the present disclosure is a bipolar plate used in a redox flow battery, comprising: a plurality of composite sheets; and a first mixture that bonds the stacked composite sheets together; each of the plurality of composite sheets comprising a resin sheet including a plurality of voids; and a second mixture that fills at least a portion of the plurality of voids in the resin sheet; and each of the first mixture and the second mixture comprises a plurality of conductive particles and a resin binder that fixes the plurality of conductive particles to the resin sheet.
[0016] The bipolar plate of the present disclosure has multiple composite sheets laminated and integrated by the first mixture. The bipolar plate of the present disclosure has excellent mechanical strength. This is because the resin sheet functions as a reinforcing material. The bipolar plate has higher mechanical strength than bipolar plates made of plastic carbon, which have been used conventionally. Bipolar plates made of plastic carbon are formed by molding a mixture of resin and carbon particles. The bipolar plate of the present disclosure has a structure in which resin sheets are stacked in layers. Therefore, the bipolar plate of the present disclosure is resistant to bending in the lamination direction of the composite sheets. The bipolar plate of the present disclosure can suppress cracking due to bending deformation during handling, for example.
[0017] The bipolar plate of the present disclosure has electrical conductivity and liquid-blocking properties. Liquid-blocking properties refer to the property of a bipolar plate that does not allow electrolyte to pass through. In the bipolar plate of the present disclosure, a plurality of conductive particles contained in the second mixture are dispersed and held within the resin sheet. Therefore, the bipolar plate of the present disclosure can ensure electrical conductivity. Furthermore, in the bipolar plate of the present disclosure, by stacking a plurality of composite sheets, voids that communicate in the stacking direction of the composite sheets are unlikely to be formed. By filling the resin sheet with the second mixture, the resin sheet has fewer voids. Therefore, the bipolar plate of the present disclosure can ensure liquid-blocking properties for electrolyte.
[0018] (2) In one embodiment of the bipolar plate, the mass ratio of the resin sheet may be 3 mass % or more and 15 mass % or less.
[0019] The above configuration makes it easy to ensure the mechanical strength and electrical conductivity of the bipolar plate.
[0020] (3) In one embodiment of the bipolar plate, the first mixture is disposed between the resin sheets of the adjacent composite sheets.
[0021] In the above embodiment, the adjacent composite sheets can be easily bonded to each other by the first mixture.
[0022] (4) As one embodiment of the bipolar plate, a third mixture is provided that forms a surface of the bipolar plate, and the third mixture includes a plurality of conductive particles and a resin binder that fixes the plurality of conductive particles to the resin sheet.
[0023] In the above embodiment, the surface of the bipolar plate is made of the third mixture, and thus the conductivity of the surface of the bipolar plate is improved.
[0024] (5) In one embodiment of the bipolar plate, the resin sheet includes a plurality of resin fibers.
[0025] The resin sheet containing a plurality of resin fibers has voids between the fibers. In the above embodiment, the voids between the fibers are filled with the second mixture.
[0026] (6) In one embodiment of the bipolar plate described in (5) above, the resin sheet may be a nonwoven fabric or a woven fabric.
[0027] The above-mentioned configuration allows more of the second mixture to fill the gaps between the fibers, thereby increasing the conductivity of the bipolar plate.
[0028] (7) In one embodiment of the bipolar plate according to (5) or (6), the plurality of resin fibers include polypropylene fibers.
[0029] The above configuration can increase the mechanical strength of the bipolar plate.
[0030] (8) In one embodiment of the bipolar plate, the number of layers of the composite sheets may be 7 or more.
[0031] The above-mentioned configuration makes it easy to ensure the mechanical strength and liquid-blocking properties of the bipolar plate.
[0032] (9) In one embodiment of the bipolar plate, the resin sheet may have a thickness of 0.1 mm or more and 2 mm or less.
[0033] The above-described configuration makes it easy to achieve a thin bipolar plate while ensuring the mechanical strength and liquid-blocking properties of the bipolar plate.
[0034] (10) In one embodiment of the bipolar plate, the thickness of the bipolar plate may be 2 mm or more and 10 mm or less.
[0035] The above-described embodiment can ensure the mechanical strength and liquid-blocking properties of the bipolar plate while realizing a thin bipolar plate.
[0036] (11) In one embodiment of the bipolar plate, the bending strength of the bipolar plate may be 0.5 MPa or more.
[0037] The above-mentioned configuration is strong against bending, and cracks are unlikely to occur in the bipolar plate.
[0038] (12) A cell frame according to an embodiment of the present disclosure includes the bipolar plate according to any one of (1) to (11) above.
[0039] The cell frame of the present disclosure includes bipolar plates that have excellent mechanical strength. Because the bipolar plates are less likely to crack during cell frame manufacturing, the cell frame of the present disclosure has excellent productivity.
[0040] (13) A cell stack according to an embodiment of the present disclosure includes the cell frame described in (12) above.
[0041] The cell stack of the present disclosure includes the cell frame of the present disclosure described above, and therefore includes bipolar plates with excellent mechanical strength. Because the bipolar plates are less likely to crack during cell stack manufacturing, the cell stack of the present disclosure has excellent productivity.
[0042] (14) A redox flow battery according to an embodiment of the present disclosure includes the cell stack described in (13) above.
[0043] The redox flow battery of the present disclosure includes the cell stack of the present disclosure described above, and therefore includes bipolar plates with excellent mechanical strength. Because the bipolar plates are less likely to crack during assembly of the redox flow battery, the redox flow battery of the present disclosure has excellent productivity.
[0044] [Details of Embodiments of the Present Disclosure] Specific examples of the bipolar plates, self-frames, cell stacks, and redox flow batteries of the present disclosure will be described with reference to the drawings. Hereinafter, the redox flow battery may be referred to as an "RF battery" in some cases. The same reference numerals in the drawings indicate the same or corresponding parts. Note that the present invention is not limited to these examples, and is defined by the claims, and is intended to include all modifications within the meaning and scope equivalent to the claims. Hereinafter, the RF battery, cell stack, and self-frame will be described first, and then the bipolar plate will be described in detail.
[0045] <RF Battery> Referring to FIG. 1, the RF battery 1 will be described. The RF battery 1 is typically connected to a power generation unit 8 and a load 9 via an AC / DC converter 7 and a substation facility 71. The RF battery 1 can charge the power generated by the power generation unit 8 or discharge the charged power to the load 9. The power generation unit 8 is a power generation facility using natural energy such as solar power generation or wind power generation, or other general power plants. The RF battery 1 is used, for example, for load leveling, momentary voltage compensation, emergency power supply, and output smoothing of natural energy power generation.
[0046] The RF battery 1 performs charge and discharge by circulating an electrolytic solution through the battery cell 100. The RF battery 1 includes a battery cell 100, a tank for storing the electrolytic solution, and a circulation flow path for circulating the electrolytic solution between the battery cell 100 and the tank. The tank has a positive electrode electrolytic solution tank 106 for storing the positive electrode electrolytic solution and a negative electrode electrolytic solution tank 107 for storing the negative electrode electrolytic solution. The circulation flow path has pipes connecting between the battery cell 100 and each tank.
[0047] For the electrolytic solution, for example, a vanadium-based electrolytic solution, a titanium-manganese-based electrolytic solution, etc. are used. In the vanadium-based electrolytic solution, both the positive electrode electrolytic solution and the negative electrode electrolytic solution contain vanadium ions as active substances. In the titanium-manganese-based electrolytic solution, the positive electrode electrolytic solution contains manganese ions as active substances, and the negative electrode electrolytic solution contains titanium ions as active substances.
[0048] (battery cell) The battery cell 100 includes a positive electrode 104, a negative electrode 105, and a diaphragm 101. The diaphragm 101 is disposed between the positive electrode 104 and the negative electrode 105. The battery cell 100 is divided into a positive electrode cell 102 and a negative electrode cell 103 by the diaphragm 101. The positive electrode 104 is disposed in the positive electrode cell 102. The negative electrode 105 is disposed in the negative electrode cell 103.
[0049] A positive electrode electrolyte is supplied to the positive electrode cell 102. A negative electrode electrolyte is supplied to the negative electrode cell 103. As shown in FIG. 1 , the RF battery 1 includes an outward pipe 108 and a return pipe 110 that connect the battery cell 100 and the positive electrode electrolyte tank 106. The RF battery 1 also includes an outward pipe 109 and a return pipe 111 that connect the battery cell 100 and the negative electrode electrolyte tank 107. The outward pipes 108 and 109 are provided with pumps 112 and 113. The positive electrode electrolyte is supplied from the positive electrode electrolyte tank 106 through the outward pipe 108 to the positive electrode cell 102 by the pump 112. The positive electrode electrolyte that has passed through the positive electrode cell 102 and is discharged from the positive electrode cell 102 is returned to the positive electrode electrolyte tank 106 through the return pipe 110. In other words, the outward pipe 108 and the return pipe 110 form a circulation flow path for the positive electrode electrolyte. The negative electrode electrolyte is supplied by a pump 113 from the negative electrode electrolyte tank 107 through an outward piping 109 to the negative electrode cell 103. The negative electrode electrolyte that has passed through the negative electrode cell 103 and is discharged from the negative electrode cell 103 is returned to the negative electrode electrolyte tank 107 through a return piping 111. In other words, the outward piping 109 and the return piping 111 form a circulation flow path for the negative electrode electrolyte.
[0050] <Cell stack> The RF battery 1 includes a cell stack 2. The cell stack 2 has a structure in which multiple battery cells 100 are stacked. For example, as shown in FIG. 2, the cell stack 2 is configured by sandwiching a sub-stack 200s between two end plates 210 on both sides and fastening the sub-stack 200s with a fastening mechanism 230. FIG. 2 shows the cell stack 2 including multiple sub-stacks 200s. The sub-stack 200s includes a stack body and supply / discharge plates 220 provided on both ends of the stack body. The stack body is formed by repeatedly stacking a cell frame 120, a positive electrode 104, a diaphragm 101, and a negative electrode 105 in this order. The supply / discharge plate 220 is connected to the outgoing pipes 108, 109 and the return pipes 110, 111 shown in FIG. 1 described above. The number of stacked battery cells 100 in the cell stack 2 can be selected as appropriate.
[0051] <Cell Frame> The cell frame 120 includes a bipolar plate 10. The cell frame 120 of this embodiment has the bipolar plate 10 and a frame body 122 provided on the outer periphery of the bipolar plate 10. As shown in FIG. 1, the bipolar plate 10 separates adjacent battery cells 100. The bipolar plate 10 is disposed between the positive electrode 104 and the negative electrode 105 of the adjacent battery cells 100. The surface of the bipolar plate 10 has a first surface facing the positive electrode 104 and a second surface facing the negative electrode 105. As shown in FIG. 2, the frame body 122 is provided on the outer periphery of the bipolar plate 10. A recess 122r is formed inside the frame body 122 by the surface of the bipolar plate 10 and the inner peripheral surface of the frame body 122. The recess 122r is formed on both sides of the bipolar plate 10. Bipolar plate 10 The positive electrode 104 is disposed in the recess 122r on the first surface side of the bipolar plate. 10 The negative electrode 105 is disposed in the recess 122r on the second surface side of the battery 10. Each recess 122r forms a cell space for each of the positive electrode cell 102 and the negative electrode cell 103 shown in FIG.
[0052] The frame 122 is made of resin. Examples of resins that form the frame 122 include polyvinyl chloride (PVC), polypropylene (PP), polyethylene (PE), and fluororesin. Examples of fluororesin include polytetrafluoroethylene (PTFE). The frame 122 is formed, for example, by injection molding a resin onto the outer periphery of the bipolar plate 10.
[0053] 1, in the cell stack 2, one battery cell 100 is provided between the bipolar plates 10 of adjacent cell frames 120. An annular sealing member 127 that prevents leakage of the electrolyte is disposed between the frame bodies 122 of each cell frame 120. The sealing member 127 is, for example, an O-ring.
[0054] As shown in FIG. 2 , the frame 122 of the cell frame 120 has liquid supply manifolds 123 and 124 and liquid discharge manifolds 125 and 126. In this example, the positive electrode electrolyte is supplied from the liquid supply manifold 123 to the positive electrode 104 via a liquid supply slit 123s. The positive electrode electrolyte supplied to the positive electrode 104 is discharged to the liquid discharge manifold 125 via a liquid discharge slit 125s. Similarly, the negative electrode electrolyte is supplied from the liquid supply manifold 124 to the negative electrode 105 via a liquid supply slit 124s. The negative electrode electrolyte supplied to the negative electrode 105 is discharged to the liquid discharge manifold 126 via a liquid discharge slit 126s. The liquid supply manifolds 123 and 124 and the liquid discharge manifolds 125 and 126 are formed to penetrate the frame 122. The liquid supply manifolds 123, 124 and the liquid discharge manifolds 125, 126 form flow paths for the respective electrolytes by stacking the cell frames 120. Each of these flow paths is connected to the outward pipes 108, 109 and the return pipes 110, 111 shown in FIG. 1 via the supply / discharge plate 220. The cell stack 2 is able to circulate the positive electrode electrolyte and the negative electrode electrolyte to each battery cell 100 via each of the above flow paths.
[0055] <Bipolar plate> A bipolar plate 10 according to an embodiment will be described with reference to FIGS. 3 to 6. One feature of the bipolar plate 10 according to the embodiment is that it has a structure in which a plurality of composite sheets 11 are stacked, as shown in FIG. 4. The bipolar plate 10 includes a plurality of composite sheets 11 shown in FIG. 5 and a first mixture 30a shown in FIG. 6. The first mixture 30a bonds the stacked composite sheets 11 together. Each of the plurality of composite sheets 11 includes a resin sheet 20 and a second mixture 30b, as shown in FIG. 6. The resin sheet 20 includes a plurality of voids 24, as shown in FIG. 6. The second mixture 30b fills at least a portion of the plurality of voids 24 in the resin sheet 20. Each of the first mixture 30a and the second mixture 30b includes a plurality of conductive particles 31 and a resin binder 32.
[0056] FIG. 4 shows a portion of the cross section IV-IV of FIG. 3. The cross section of the bipolar plate 10 shown in FIG. 4 is a cross section cut along the thickness direction of the bipolar plate 10. The thickness direction of the bipolar plate 10 is a direction perpendicular to the surface of the bipolar plate 10. The thickness direction of the bipolar plate 10 corresponds to the stacking direction of the composite sheets 11. FIG. 5 shows an enlarged cross section of adjacent composite sheets 11. FIG. 6 shows an enlarged view of the area surrounded by line VI in FIG. 5. For convenience, in FIGS. 5 and 6, the resin binder 32 is indicated by hatching. In FIGS. 5 and 6, the configuration of the resin sheet 20, the shape and size of the voids 24, and the configurations of the first mixture 30a and the second mixture 30b are shown in a simplified schematic manner. In the figures, arrow Z indicates the thickness direction.
[0057] The bipolar plate 10 has excellent mechanical strength because the resin sheet 20 functions as a reinforcing material. The bipolar plate 10 is electrically conductive and has liquid-blocking properties that prevent the passage of electrolyte.
[0058] The shape of the bipolar plate 10 can be selected as appropriate. In this example, the bipolar plate 10 is rectangular in plan view. The thickness of the bipolar plate 10 is, for example, 2 mm or more and 10 mm or less. The thicker the bipolar plate 10, the higher the mechanical strength of the bipolar plate 10. Furthermore, the thicker the bipolar plate 10, the less likely it is that voids that communicate with each other in the thickness direction of the bipolar plate 10, i.e., the stacking direction of the composite sheet 11, will be formed. This improves the liquid-blocking properties of the bipolar plate 10. If the thickness of the bipolar plate 10 is 2 mm or more, it is easy to ensure the mechanical strength and liquid-blocking properties of the bipolar plate 10. If the thickness of the bipolar plate 10 is 10 mm or less, the bipolar plate 10 can be made thinner. By making the bipolar plate 10 thinner, the cell stack 2 can be made smaller, and ultimately the RF battery 1 can be made smaller. Furthermore, the thinner the bipolar plate 10, the lower the electrical resistance of the bipolar plate 10. The thickness of the bipolar plate 10 may further be 4 mm or more and 8 mm or less.
[0059] The bending strength of the bipolar plate 10 is, for example, 0.5 MPa or more. If the bending strength of the bipolar plate 10 is 0.5 MPa or more, the bipolar plate 10 is strong against bending and is less likely to crack. The bending strength is measured by a three-point bending test. The bending strength of the bipolar plate 10 is, for example, 0.8 MPa or more, preferably 1.0 MPa or more. The bending strength of the bipolar plate 10 may further be 2 MPa or more, 5 MPa or more. The upper limit of the bending strength of the bipolar plate 10 is practically, for example, 40 MPa. That is, the bending strength of the bipolar plate 10 is, for example, 0.5 MPa or more and 40 MPa or less.
[0060] The tensile strength of the bipolar plate 10 is, for example, 2 MPa or more. If the tensile strength of the bipolar plate 10 is 2 MPa or more, the bipolar plate has sufficient tensile strength. The tensile strength of the bipolar plate 10 may further be 6 MPa or more, or 20 MPa or more. The upper limit of the tensile strength of the bipolar plate 10 is practically, for example, 40 MPa. That is, the tensile strength of the bipolar plate 10 is, for example, 2 MPa or more and 40 MPa or less.
[0061] The volume resistivity of the bipolar plate 10 is, for example, 2.0 Ω·cm or less. If the volume resistivity of the bipolar plate 10 is 2.0 Ω·cm or less, the bipolar plate has good conductivity. The volume resistivity of the bipolar plate 10 is, for example, 1.5 Ω·cm or less, and preferably 1.0 Ω·cm or less. The volume resistivity of the bipolar plate 10 may further be 0.5 Ω·cm or less, 0.3 Ω·cm or less, or 0.2 Ω·cm or less. The lower limit of the volume resistivity of the bipolar plate 10 is, for example, 0.05 Ω·cm. That is, the volume resistivity of the bipolar plate 10 is, for example, 0.05 Ω·cm or more and 2.0 Ω·cm or less. The volume resistivity is the volume resistivity in the plane direction of the bipolar plate. The plane direction of the bipolar plate is the direction perpendicular to the thickness direction of the bipolar plate.
[0062] (composite sheet) As shown in FIG. 6 , the composite sheet 11 includes a second mixture 30b filled in the voids 24 of the resin sheet 20. In the resin sheet 20, at least a portion of the voids 24 is filled with the second mixture 30b. Therefore, in the resin sheet 20, there are few voids 24 that are not filled with the second mixture 30b. In this example, the second mixture 30b fills almost all of the voids 24 of the resin sheet 20. In other words, the second mixture 30b is substantially filled throughout the entire interior of the resin sheet 20. The conductivity of the bipolar plate 10 can be ensured by maintaining the plurality of conductive particles 31 contained in the second mixture 30b in a dispersed state inside the resin sheet 20.
[0063] Furthermore, as shown in FIG. 4 , by stacking multiple composite sheets 11, voids 24 (see FIG. 6 ) that communicate with each other in the stacking direction of the composite sheets 11 are less likely to be formed. As a result, the liquid-blocking properties of the bipolar plate 10 can be ensured. The number of stacked composite sheets 11 can be appropriately selected. In FIG. 4 , for convenience of explanation, the number of stacked composite sheets 11 is set to three. The number of stacked composite sheets 11 is, for example, seven or more. The number of stacked composite sheets 11 matches the number of resin sheets 20. The greater the number of stacked composite sheets 11, the greater the number of resin sheets 20. This can increase the mechanical strength of the bipolar plate 10. Furthermore, the greater the number of stacked composite sheets 11, the less likely voids 24 that communicate with each other in the stacking direction of the composite sheets 11 are formed. This can improve the liquid-blocking properties. If the number of stacked composite sheets 11 is seven or more, it is easy to ensure the mechanical strength and liquid-blocking properties of the bipolar plate 10. The upper limit of the number of stacked composite sheets 11 is, for example, 80. If the number of layers of the composite sheet 11 is 80 or less, it is possible to reduce the thickness of the bipolar plate 10. The number of layers of the composite sheet 11 may further be 15 or more and 60 or less, or 20 or more and 50 or less.
[0064] (resin sheet) The resin sheet 20 is a sheet made of resin. The resin sheet 20 has a three-dimensional structure including a plurality of voids 24 (see FIG. 6). The voids 24 comprise open voids that are continuous from the surface to the interior of the resin sheet 20. The open voids are voids that connect the interior of the resin sheet 20 to the exterior. Furthermore, the voids 24 may include closed voids that are not open to the surface of the resin sheet 20 but are isolated within the resin sheet 20. The closed voids are voids that exist inside the resin sheet 20 and are not connected to the exterior. The resin sheet 20 may be in any form, such as a fiber aggregate or a sponge. Known resin sheets can be used for the resin sheet 20. The fiber aggregate will be described later.
[0065] The resin sheet 20 preferably has resistance to the electrolyte and excellent mechanical properties. Examples of resins that form the resin sheet 20 include PP, PE, PTFE, and polyamide (PA). Polyamides include aramid. Among these resins, PP is preferred from the viewpoints of mechanical properties, resistance to the electrolyte, cost, and the like.
[0066] The mass percentage of the resin sheet 20 is, for example, 3% by mass or more and 15% by mass or less. The higher the mass percentage of the resin sheet 20, the higher the mechanical strength of the bipolar plate 10. If the mass percentage of the resin sheet 20 is 3% by mass or more, it is easier to ensure the mechanical strength of the bipolar plate 10. If the mass percentage of the resin sheet 20 is high, the electrical resistance of the bipolar plate 10 increases. If the mass percentage of the resin sheet 20 is 15% by mass or less, the electrical resistance of the bipolar plate 10 can be reduced. The mass percentage of the resin sheet 20 may further be 7% by mass or more and 9.5% by mass or less.
[0067] The mass ratio of the resin sheet 20 is the ratio of the mass of the resin sheet 20 to the mass of the entire bipolar plate 10, which is 100%. The mass ratio of the resin sheet 20 is expressed as [(Ma / M) × 100], where M is the mass of the bipolar plate 10 and Ma is the mass of the resin sheet 20. The mass of the resin sheet 20 is the mass of the composite sheet 11 excluding the first mixture 30a and the second mixture 30b. The mass of the resin sheet 20 is measured, for example, as follows: The bipolar plate 10 is immersed in a solvent to dissolve the resin binder 32 contained in each of the mixtures. A solvent that dissolves the resin binder 32 but not the resin sheet 20 is selected. Examples of the solvent that can be used include toluene, xylene, ester, and benzene. After dissolving the resin binder 32, the resin sheet 20 is washed. By washing the resin sheet 20, the conductive particles 31 adhering to the resin sheet 20 are washed away. After the resin sheet 20 is dried, the mass of the resin sheet 20 is measured.
[0068] The thickness of the resin sheet 20 is, for example, 0.1 mm or more and 2 mm or less. The thicker the resin sheet 20, the more improved the mechanical strength of the bipolar plate 10. Furthermore, the thicker the resin sheet 20, the less likely it is that voids 24 (see FIG. 6) that communicate in the thickness direction of the resin sheet 20 will be formed. This improves the liquid-blocking properties. If the thickness of the resin sheet 20 is 0.1 mm or more, it is easy to ensure the mechanical strength and liquid-blocking properties of the bipolar plate 10. If the thickness of the resin sheet 20 is 2 mm or less, the bipolar plate 10 can be made thinner. The thickness of the resin sheet 20 may further be 0.15 mm or more and 1 mm or less. The thickness of the resin sheet 20 here refers to the thickness of the resin sheet 20 in an uncompressed state.
[0069] The porosity of the resin sheet 20 is, for example, 20% by volume or more and 95% by volume or less. The higher the porosity of the resin sheet 20, the higher the filling rate of the second mixture 30b filled inside the resin sheet 20 can be. In other words, the mass proportion of the conductive particles 31 increases. As a result, the conductivity of the bipolar plate 10 is improved. When the porosity of the resin sheet 20 is 20% by volume or more, the conductivity of the bipolar plate 10 can be increased. When the porosity of the resin sheet 20 is high, the mechanical strength of the resin sheet 20 decreases. In other words, the mechanical strength of the bipolar plate 10 decreases. When the porosity of the resin sheet 20 is 95% by volume or less, the mechanical strength of the bipolar plate 10 can be easily ensured. The porosity of the resin sheet 20 may further be 30% by volume or more and 90% by volume or less.
[0070] The porosity of the resin sheet 20 is the ratio of the volume of voids when the apparent volume of the resin sheet 20 is taken as 100%. The porosity of the resin sheet 20 is expressed as [(Vp / V) × 100], where V is the apparent volume of the resin sheet 20 and Vp is the volume of the voids. The apparent volume is the volume of the resin sheet 20 including the voids. The porosity of the resin sheet 20 can be measured using, for example, the Archimedes method. The porosity of the resin sheet 20 is measured by removing each of the above mixtures from the resin sheet 20 using the above solvent.
[0071] <Fiber assembly> In this example, the resin sheet 20 is a fiber assembly including a plurality of resin fibers 22, as shown in FIG. 5. The fiber assembly is a sheet constituted by a plurality of resin fibers 22. As shown in FIG. 6, the fiber assembly has voids 24 between the resin fibers 22. The voids 24 are filled with the second mixture 30b. In other words, when the resin sheet 20 is a fiber assembly, the voids 24 between the resin fibers 22 are filled with the second mixture 30b, thereby holding a plurality of conductive particles 31 inside the fiber assembly.
[0072] Examples of fiber assemblies include nonwoven fabric, woven fabric, and paper. Nonwoven fabric and woven fabric maintain their shape by entangling multiple resin fibers 22. Paper maintains its shape by binding multiple resin fibers 22 together. Nonwoven fabric is made by entangling individual resin fibers 22. Woven fabric is made by weaving threads in which multiple resin fibers 22 are twisted together. Nonwoven fabric and woven fabric have more voids 24 between the resin fibers 22 than paper, which contains a binder that binds the resin fibers 22 together. Therefore, nonwoven fabric and woven fabric have a relatively high void ratio. When the resin sheet 20 is nonwoven fabric or woven fabric, the second mixture 30b filled inside the resin sheet 20 tends to be increased. As a result, the mass proportion of the conductive particles 31 can be increased. In particular, nonwoven fabric is advantageous over woven fabric in that fine voids are uniformly distributed between the resin fibers 22. Known fiber assemblies can be used.
[0073] The resin fibers 22 are, for example, fibers of PP, PE, PTFE, PA, etc. From the viewpoints of mechanical properties, resistance to the electrolyte, cost, etc., PP fibers are preferred as the resin fibers 22. A fiber assembly containing PP fibers can easily ensure mechanical strength.
[0074] The average diameter of the resin fibers 22 is, for example, 5 μm or more and 50 μm or less. When the average diameter of the resin fibers 22 is 5 μm or more, it is easy to ensure the mechanical strength of the fiber assembly. When the average diameter of the resin fibers 22 is 50 μm or less, the resin fibers 22 can have appropriate flexibility. Therefore, the fiber assembly has good flexibility. The average diameter of the resin fibers 22 may further be 10 μm or more and 40 μm or less.
[0075] The average diameter of the resin fibers 22 can be measured, for example, as follows. The cross section of the fiber assembly is observed with a scanning electron microscope (SEM). The SEM image is subjected to image analysis to calculate the cross-sectional area of the resin fibers 22. The cross section of the resin fibers 22 is a cross section perpendicular to the longitudinal direction of the resin fibers 22. The diameter of the resin fibers 22 is the diameter of a circle having an area equal to the cross-sectional area of the resin fibers 22. The average diameter of the resin fibers 22 is, for example, the average value of the diameters of 10 or more resin fibers 22. The number of resin fibers 22 measured may further be 20 or more, or 30 or more. The acceleration voltage of the SEM during observation is, for example, 10 kV or more and 20 kV or less. The magnification of the SEM during observation is, for example, 100 times or more and 500 times or less.
[0076] (mixture) As shown in FIG. 6 , each of the first mixture 30a and the second mixture 30b contains a plurality of conductive particles 31 and a resin binder 32. The first mixture 30a bonds adjacent composite sheets 11 together. The resin binder 32 contained in the first mixture 30a functions as an adhesive that bonds the composite sheets 11 together. In this example, the first mixture 30a and the second mixture 30b are the same mixture. When the first mixture 30a and the second mixture 30b are the same, the materials of the conductive particles 31 and the resin binder 32 contained in the first mixture 30a and the second mixture 30b are the same. When the first mixture 30a and the second mixture 30b are the same, the content of the conductive particles 31 and the content of the resin binder 32 in the first mixture 30a are substantially the same as the content of the conductive particles 31 and the content of the resin binder 32 in the second mixture 30b. The content of conductive particles 31 being substantially the same means that the ratio of the content of conductive particles 31 in the first mixture 30a to the content of conductive particles 31 in the second mixture 30b is within a range of 0.9 to 1.1. The content of resin binder 32 being substantially the same means that the ratio of the content of resin binder 32 in the first mixture 30a to the content of resin binder 32 in the second mixture 30b is within a range of 0.9 to 1.1. In addition, in this example, adjacent composite sheets 11 are in contact with each other. The first mixture 30a is a portion of the second mixture 30b filled in the voids 24 of each resin sheet 20 that forms the boundary between adjacent composite sheets 11. In other words, a portion of the second mixture 30b filled in the voids 24 open to the surface of the resin sheet 20 also serves as the first mixture 30a.
[0077] <Conductive particles> The conductive particles 31 are conductive and have a predetermined resistance to the electrolyte. The conductive particles 31 are, for example, carbon particles or metal particles. The carbon constituting the carbon particles is, for example, graphite or carbon black. The metal constituting the metal particles is, for example, a metal selected from the group consisting of gold, silver, copper, tin, iron, nickel, chromium, zinc, aluminum, and titanium, or an alloy thereof. From the viewpoints of conductivity, resistance to the electrolyte, cost, etc., the conductive particles 31 are preferably carbon particles.
[0078] The conductive particles 31 are maintained in a dispersed state within the resin sheet 20 by the resin binder 32. The shape of the conductive particles 31 is typically spherical. The shape of the conductive particles 31 may be acicular, thin plate-like, or the like, in addition to spherical. The average particle size of the conductive particles 31 is, for example, 20 nm or more and 100 μm or less. The average particle size of the conductive particles 31 is preferably smaller than the average pore size of the resin sheet 20. The average pore size of the resin sheet 20 can be measured, for example, by mercury intrusion porosimetry. The average pore size of the resin sheet 20 is measured by removing each of the above mixtures from the resin sheet 20 using the above-mentioned solvent.
[0079] The average particle size of the conductive particles 31 can be measured, for example, as follows: The cross section of the composite sheet 11 is observed with an SEM. The SEM image is analyzed to calculate the cross-sectional area of the conductive particles 31. The particle size of the conductive particles 31 is the diameter of a circle having an area equal to the cross-sectional area of the conductive particles 31. The average particle size of the conductive particles 31 is, for example, the average value of the particle sizes of 20 or more conductive particles 31. The number of conductive particles 31 measured may further be 50 or more, or 100 or more. The acceleration voltage of the SEM during observation is, for example, 10 kV or more and 20 kV or less. The magnification of the SEM during observation is, for example, 100 times or more and 500 times or less.
[0080] The mass percentage of the conductive particles 31 is, for example, 55% by mass or more and 95% by mass or less. The higher the mass percentage of the conductive particles 31, the better the conductivity of the bipolar plate 10. When the mass percentage of the conductive particles 31 is 55% by mass or more, it is easier to ensure the conductivity of the bipolar plate 10. When the mass percentage of the conductive particles 31 is high, the proportion of the resin binder 32 is likely to decrease. When the mass percentage of the conductive particles 31 is 95% by mass or less, it is possible to suppress the decrease of the resin binder 32. The mass percentage of the conductive particles 31 may further be 60% by mass or more and 85% by mass or less, or 60% by mass or more and 70% by mass or less. The mass percentage of the conductive particles 31 is the proportion of the mass of the conductive particles 31 when the mass of the entire bipolar plate 10 is 100%. The mass percentage of the conductive particles 31 is expressed as [(Mb / M) × 100], where M is the mass of the bipolar plate 10 and Mb is the mass of the conductive particles 31. The mass of the conductive particles 31 is measured, for example, as follows: The resin binder 32 contained in each of the mixtures is dissolved using the solvent described above. The mass of the conductive particles 31 separated from the resin sheet 20 is measured.
[0081] <Resin binder> The resin binder 32 fixes the plurality of conductive particles 31 to the resin sheet 20. The resin binder 32 is a resin such as PE, PP, chlorinated polyolefin, PTFE, perfluoroalkoxyalkane (PFA), perfluoroethylenepropene copolymer (FEP), or polyphenylene sulfide (PPS). The resin binder 32 may be the same as or different from the resin constituting the resin sheet 20. From a manufacturing standpoint, it is preferable that the softening point of the resin binder 32 is lower than the softening point of the resin sheet 20. The reason for this will be described later.
[0082] The mass percentage of the resin binder 32 is, for example, 5% by mass or more and 40% by mass or less. When the mass percentage of the resin binder 32 is 5% by mass or more, the resin binder 32 can easily fix the conductive particles 31 to the resin sheet 20. When the mass percentage of the resin binder 32 is 40% by mass or less, the proportion of the conductive particles 31 can be increased. As a result, the conductivity of the bipolar plate 10 is improved. The mass percentage of the resin binder 32 may further be 10% by mass or more and 30% by mass or less, or 20% by mass or more and 30% by mass or less. The mass percentage of the resin binder 32 is the mass percentage of the resin binder 32 when the mass of the entire bipolar plate 10 is 100%. The mass percentage of the resin binder 32 is expressed as [(Mc / M) × 100], where M is the mass of the bipolar plate 10 and Mc is the mass of the resin binder 32. The mass percentage of the resin binder 32 can be calculated, for example, by subtracting the mass percentage of the resin sheet 20 and the mass percentage of the conductive particles 31 from 100%.
[0083] [Variations] Modified examples of the bipolar plate 10 will be described with reference to FIGS. 7 to 10 . Similar to FIG. 4 , FIG. 7 shows a portion of the cross section of the bipolar plate 10. Similar to FIG. 5 , FIG. 8 shows an enlarged cross section of adjacent composite sheets 11. Similar to FIG. 5 , FIG. 9 shows an enlarged view of the area surrounded by line IX in FIG. 8 . FIG. 10 shows an enlarged cross section of the surface portion of the bipolar plate 10. For convenience, the resin binder 32 is indicated by hatching in FIGS. 8 to 10 . In FIGS. 8 to 10 , the configuration of the resin sheet 20, the shape and size of the voids 24, and the configurations of the first mixture 30a and the second mixture 30b are shown in a simplified schematic form. The bipolar plate 10 according to the modified example differs from the above-described embodiment in that the first mixture 30a is located between the resin sheets 20 of adjacent composite sheets 11. The following description of the modified bipolar plate 10 will focus on the differences from the above-described embodiment, and similar details will not be repeated.
[0084] (First mixture 30a) As shown in FIGS. 7 and 8 , the first mixture 30a is disposed between the resin sheets 20 of adjacent composite sheets 11. The first mixture 30a is formed in a layered form from a mixture containing a plurality of conductive particles 31 and a resin binder 32. As shown in FIG. 9 , the first mixture 30a does not fill the voids 24 of the resin sheet 20 but is exposed on the surface of the resin sheet 20. Adjacent composite sheets 11 are not in contact with each other but are joined via the first mixture 30a. When the first mixture 30a is disposed between the resin sheets 20, the amount of the mixture contained in the bipolar plate 10 increases. The first mixture 30a may be the same as or different from the second mixture 30b. When the first mixture 30a and the second mixture 30b are different, for example, the material of the conductive particles 31 contained in the first mixture 30a may be different from the material of the conductive particles 31 contained in the second mixture 30b. When the first mixture 30a and the second mixture 30b are different, for example, the material of the resin binder 32 contained in the first mixture 30a may be different from the material of the resin binder 32 contained in the second mixture 30b. In a modified example, the first mixture 30a and the second mixture 30b are the same mixture. That is, the material of the conductive particles 31 and the material of the resin binder 32 contained in the first mixture 30a and the second mixture 30b are the same. Furthermore, the content of the conductive particles 31 in the first mixture 30a is substantially the same as the content of the conductive particles 31 in the second mixture 30b. The content of the resin binder 32 in the first mixture 30a is substantially the same as the content of the resin binder 32 in the second mixture 30b.
[0085] In a modified example, the first mixture 30a functions as an adhesive layer that bonds the composite sheets 11 together. The thickness of the first mixture 30a is, for example, 5 μm or more and 300 μm or less. The thickness of the first mixture 30a is the distance between the resin sheets 20 of adjacent composite sheets 11. In other words, it is the distance between the surfaces of the resin sheets 20 that face each other. When the thickness of the first mixture 30a is 5 μm or more, the first mixture 30a easily functions as an adhesive layer. When the thickness of the first mixture 30a is 300 μm or less, the bipolar plate 10 can be made thinner. The thickness of the first mixture 30a may further be 10 μm or more and 250 μm or less.
[0086] Furthermore, in this modification, as shown in FIG. 7, a third mixture 30c is provided on the surface of the bipolar plate 10. The third mixture 30c covers the surface of the composite sheet 11 that is arranged outermost in the stacking direction among the multiple composite sheets 11. As shown in FIG. 10, the third mixture 30c is a mixture containing multiple conductive particles 31 and a resin binder 32. The third mixture 30c is formed into a layer shape with the above mixture. The third mixture 30c does not fill the voids 24 of the resin sheet 20, but is exposed on the surface of the resin sheet 20.
[0087] The third mixture 30c may be the same as or different from the first mixture 30a and the second mixture 30b. In a modified example, the first mixture 30a, the second mixture 30b, and the third mixture 30c are the same mixture. That is, the material of the conductive particles 31 and the material of the resin binder 32 contained in each of the first mixture 30a, the second mixture 30b, and the third mixture 30c are the same. Furthermore, the content of the conductive particles 31 in the first mixture 30a, the content of the conductive particles 31 in the second mixture 30b, and the content of the conductive particles 31 in the third mixture 30c are substantially the same. When the ratio of the content of conductive particles 31 in the first mixture 30a to the content of conductive particles 31 in the second mixture 30b, the ratio of the content of conductive particles 31 in the first mixture 30a to the content of conductive particles 31 in the third mixture 30c, and the ratio of the content of conductive particles 31 in the second mixture 30b to the content of conductive particles 31 in the third mixture 30c are each within the range of 0.9 to 1.1, the contents of conductive particles 31 are considered to be substantially the same. The contents of resin binder 32 in the first mixture 30a, the second mixture 30b, and the third mixture 30c are substantially the same. When the ratio of the resin binder 32 content in the first mixture 30a to the resin binder 32 content in the second mixture 30b, the ratio of the resin binder 32 content in the first mixture 30a to the resin binder 32 content in the third mixture 30c, and the ratio of the resin binder 32 content in the second mixture 30b to the resin binder 32 content in the third mixture 30c are each within the range of 0.9 or more and 1.1 or less, the resin binder 32 contents are considered to be substantially the same.
[0088] {Effects of the embodiment} The bipolar plate 10 according to the embodiment has excellent mechanical strength because the resin sheet 20 functions as a reinforcing material. In particular, because the resin sheet 20 is laminated in the thickness direction of the bipolar plate 10, the bipolar plate 10 has bending resistance and is difficult to crack.
[0089] Furthermore, in the bipolar plate 10 according to the modified example, the first mixture 30a makes it easy to bond adjacent composite sheets 11 together. In the bipolar plate 10 according to the modified example, the surface of the bipolar plate 10 is made of the third mixture 30c. In other words, the surface portion of the bipolar plate 10 does not include the resin sheet 20. This improves the conductivity of the surface of the bipolar plate 10.
[0090] <Manufacturing method of bipolar plate> The bipolar plate 10 according to the embodiment can be manufactured by, for example, a manufacturing method including the following steps: The manufacturing method for the bipolar plate includes a step of producing a laminate in which conductive compound sheets and resin sheets are alternately stacked, and a step of pressing the laminate.
[0091] (Step of producing laminate) The conductive compound sheet can be produced by using a mixture of multiple conductive particles and a resin binder as a raw material and molding the raw material into a sheet. The conductive compound sheet can be molded using, for example, an extruder. The laminate can be produced by alternately stacking the required number of conductive compound sheets and resin sheets.
[0092] (Step of pressing the laminate) The laminate is heated and pressed in the stacking direction to bond the stacked composite sheets together. For example, the laminate is placed in a mold, and the mold is heated to press the laminate while heating it. The heating temperature during pressing is set to a temperature equal to or higher than the melting point of the resin binder contained in the conductive compound sheet. As the resin binder melts, the conductive particles are filled into the resin sheet together with the molten resin binder. After pressing the laminate, the laminate is cooled to obtain a bipolar plate in which multiple composite sheets are stacked. As the molten resin binder cools and solidifies, the conductive particles are fixed to the resin sheet and adjacent composite sheets are bonded together. The mixtures that make up the conductive compound sheet are the first mixture, second mixture, and third mixture described above that will constitute the bipolar plate when it is completed.
[0093] Furthermore, the pressing conditions are preferably a heating temperature and pressing time that prevent the resin sheet from becoming molten, in order to maintain the shape of the resin sheet. Maintaining the shape of the resin sheet can prevent a decrease in the mechanical strength of the resin sheet. Therefore, the softening point of the resin binder is preferably lower than that of the resin that constitutes the resin sheet. In other words, the softening point of the resin that constitutes the resin sheet is preferably higher than that of the resin binder. For example, the resin binder can be polyethylene, and the resin that constitutes the resin sheet can be polypropylene. In this case, the heating temperature during pressing is, for example, 150°C or higher and 200°C or lower. The pressing time is, for example, 3 minutes or higher and 15 minutes or lower.
[0094] [Test Example 1] A bipolar plate sample was prepared using the composite sheet.
[0095] A resin sheet and a sheet of conductive compound were prepared. The resin sheet was a nonwoven fabric made of polypropylene fibers. The thickness of the nonwoven fabric was 0.5 mm. This thickness was measured in its natural state, i.e., without any external force acting on it. The average diameter of the polypropylene fibers was 10 μm. The melting point of polypropylene was 160°C.
[0096] Carbon particles and polyethylene were prepared as raw materials for the conductive compound. The mixture of carbon particles and polyethylene was extruded using an extruder to produce a conductive compound sheet. The thickness of the conductive compound sheet was 0.5 mm. The average particle size of the carbon particles was 20 μm. The melting point of the polyethylene was 130°C. The area of the conductive compound sheet was the same as the area of the nonwoven fabric used in the resin sheet.
[0097] A laminate was produced by alternately stacking nonwoven fabric made of polypropylene fiber and sheets of conductive compound. One layer consisted of one sheet of nonwoven fabric and one sheet of conductive compound, and 10 layers were stacked.
[0098] The mass proportions of the nonwoven fabric, the carbon particles, and the polyethylene were adjusted to the mass proportions shown in Table 1. In Test Example 1, the mass proportion of the nonwoven fabric was adjusted by changing the porosity of the nonwoven fabric. For Samples No. 1 to No. 3, the mass proportions of the carbon particles and polyethylene constituting the conductive compound sheet were adjusted so that the mass proportion of polyethylene in the entire bipolar plate was 30 mass%. For Samples No. 4 to No. 7 Regarding the bipolar plate, the mass proportions of the carbon particles and polyethylene constituting the conductive compound sheet were adjusted so that the mass proportion of polyethylene in the entire bipolar plate was 20 mass %.
[0099] The obtained laminate was placed in a mold and pressed to produce a bipolar plate. The heating temperature during pressing was 150°C. The pressing time was 10 minutes. The pressing pressure was 40 MPa. The obtained bipolar plate was punched out to a predetermined size, and samples No. 1 to No. 7 A bipolar plate was obtained.
[0100] The thickness of the bipolar plates of samples No. 1 to No. 7 is 3 mm. The area of the bipolar plates of samples No. 1 to No. 7 is 6000 mm. 2 The bipolar plates of Samples No. 1 to No. 7 were observed under a microscope, cut in the thickness direction, to reveal a structure in which composite sheets were stacked in the thickness direction of the bipolar plate. The composite sheet had 10 layers. The composite sheet included a nonwoven fabric resin sheet and a second mixture filled in the voids in the nonwoven fabric. Furthermore, all the bipolar plates of the samples had the first mixture between the resin sheets and the third mixture on the surface of the bipolar plate, similar to the variations shown in Figures 7 to 10. The first, second, and third mixtures were composed of carbon particles and polyethylene that constitute the conductive compound sheets.
[0101] For comparison, a bipolar plate made of plastic carbon was produced by molding a mixture of carbon particles and polyethylene. The mass proportions of the carbon particles and polyethylene were adjusted to the mass proportions shown in Table 1. This bipolar plate was designated Sample No. 10. The bipolar plate of Sample No. 10 did not contain a nonwoven fabric as a resin sheet. The thickness of the bipolar plate of Sample No. 10 was 3 mm. The area of the bipolar plate of Sample No. 10 was the same as the areas of the bipolar plates of Samples No. 1 to No. 7.
[0102] The mechanical strength and electrical conductivity of the bipolar plate of each sample were evaluated. The mechanical strength was evaluated by measuring bending strength and tensile strength. The electrical conductivity was evaluated by measuring volume resistivity. The results are shown in Table 1.
[0103] The bending strength of the bipolar plates was measured in accordance with JIS K7171:2016. Here, bending strength was determined by a three-point bending test. The test specimens were stored for 12 hours in a constant temperature and humidity chamber set at 23°C and 50% relative humidity in accordance with JIS K7100:1999. The test specimens were 10 mm wide and 80 mm long. The support distance was 64 mm. A 10 mm diameter pressure bar was lowered at a speed of 20 mm / min to apply a load to the center of the specimen, and the maximum load P (N) was measured. The measurement device used was a Tensilon RTE-1210 manufactured by Orientec Co., Ltd. The tensile strength of the bipolar plates was measured in accordance with JIS K7161:2014. The test specimens were JIS No. 3 dumbbell size. The measurement device used was a Tensilon RTE-1210 manufactured by Orientec Co., Ltd. The tensile test was performed at a tensile speed of 5 mm / min.
[0104] The volume resistivity of the bipolar plate was measured by the four-terminal method. The measurement device used was a digital multimeter DME1600 manufactured by Kikusui Electronics Co., Ltd. The size of the test piece was 50 mm wide x 50 mm long. The measured volume resistivity was the volume resistivity in the plane direction of the bipolar plate.
[0105] [Table 1]
[0106] The results shown in Table 1 show that bipolar plates Nos. 1 to 7, which have a laminated composite sheet structure, have higher bending strength and tensile strength and are superior in mechanical strength compared to bipolar plate No. 10, which is made of plastic carbon. The reason why samples Nos. 1 to 7 have higher mechanical strength compared to sample No. 10 is thought to be because the nonwoven fabric contained in the composite sheet functions as a reinforcing material.
[0107] Furthermore, the results shown in Table 1 indicate that the higher the mass fraction of nonwoven fabric, the higher the bending strength and tensile strength, and the improved mechanical strength. For example, Samples No. 2 to No. 7 have a bending strength of 0.5 MPa or more and a tensile strength of 2.0 MPa or more, and even a bending strength of 1.0 MPa or more and a tensile strength of 6.0 MPa or more, demonstrating excellent mechanical strength. In particular, Samples No. 3 to No. 7 have a bending strength of 2.0 MPa or more and a tensile strength of 20 MPa or more, demonstrating even better mechanical strength. On the other hand, the lower the mass fraction of nonwoven fabric, the higher the in-plane volume resistivity and the improved electrical conductivity. For example, Samples No. 1 to No. 6 have a in-plane volume resistivity of 1.5 Ω·cm or less, and even 1.0 Ω·cm or less, demonstrating excellent electrical conductivity. In particular, Samples No. 1 to No. 5 have a in-plane volume resistivity of 0.5 Ω·cm or less, demonstrating even better electrical conductivity. Compared with samples No. 1 and No. 6, samples No. 2 to No. 5 have a better balance between mechanical strength and electrical conductivity.
[0108] Furthermore, the liquid-blocking properties of the bipolar plates were evaluated for all samples No. 1 to No. 7. As a result, it was found that all samples had liquid-blocking properties. The liquid-blocking properties were evaluated as follows: A test battery cell was constructed using the bipolar plates of each sample. A charge / discharge test was performed using the test battery cell to confirm that the battery cell operated normally. If the battery cell operated normally in the charge / discharge test, the bipolar plate was evaluated as having liquid-blocking properties. [Explanation of symbols]
[0109] 1 RF battery 2 Cell stack 10 Bipolar Plate 11 Composite Sheet 20 resin sheet, 22 resin fiber, 24 void 30a first mixture, 30b second mixture, 30c third mixture 31 conductive particles, 32 resin binder 7 AC / DC converters, 71 substation equipment 8 power generation unit, 9 load 100 battery cells 101 diaphragm, 102 positive electrode cell, 103 negative electrode cell 104 positive electrode, 105 negative electrode 106 positive electrode electrolyte tank, 107 negative electrode electrolyte tank 108,109 Outward piping, 110,111 Return piping 112,113 Pump 120 Cell Frame 122 frame body, 122r recess 123,124 Supply manifold, 125,126 Drain manifold 123s, 124s supply slit, 125s, 126s drain slit 127 Sealing material 200s Substack 210 end plate, 220 supply / discharge plate, 230 tightening mechanism
Claims
1. A bipolar plate for use in a redox flow battery, comprising: A plurality of composite sheets; A first mixture that bonds the laminated composite sheets together; a third mixture constituting a surface of the bipolar plate; Each of the plurality of composite sheets is A resin sheet including a plurality of voids; a second mixture filled in at least a portion of the plurality of voids of the resin sheet; Each of the first mixture and the second mixture is A plurality of conductive particles; a resin binder that fixes the plurality of conductive particles to the resin sheet, The third mixture is A plurality of conductive particles; and a resin binder that fixes the plurality of conductive particles to the resin sheet. Bipolar plate.
2. A bipolar plate for use in a redox flow battery, comprising: A plurality of composite sheets; A first mixture that bonds the laminated composite sheets together, Each of the plurality of composite sheets is A resin sheet including a plurality of voids; a second mixture filled in at least a portion of the plurality of voids of the resin sheet; Each of the first mixture and the second mixture is A plurality of conductive particles; a resin binder that fixes the plurality of conductive particles to the resin sheet, The number of layers of the composite sheet is 7 or more. Bipolar plate.
3. a third mixture constituting a surface of the bipolar plate; The third mixture is A plurality of conductive particles; 3. The bipolar plate of claim 2, further comprising a resin binder that secures the plurality of conductive particles to the resin sheet.
4. The bipolar plate according to claim 1 , wherein a mass percentage of the resin sheet is 3 mass % or more and 15 mass % or less.
5. The bipolar plate according to claim 1 , wherein the first mixture is disposed between the resin sheets of adjacent ones of the composite sheets.
6. The bipolar plate according to claim 1 , wherein the resin sheet includes a plurality of resin fibers.
7. The bipolar plate according to claim 6 , wherein the resin sheet is a nonwoven fabric or a woven fabric.
8. The bipolar plate according to claim 6 or claim 7, wherein the plurality of resin fibers includes polypropylene fibers.
9. The bipolar plate according to claim 1 , wherein the resin sheet has a thickness of 0.1 mm or more and 2 mm or less.
10. The bipolar plate according to any one of claims 1 to 9, wherein the bipolar plate has a thickness of 2 mm or more and 10 mm or less.
11. The bipolar plate according to any one of claims 1 to 10, wherein the bipolar plate has a bending strength of 0.5 MPa or more.
12. Equipped with a bipolar plate according to any one of claims 1 to 11. Cell frame.
13. A cell frame according to claim 12, Cell stack.
14. A cell stack according to claim 13, Redox flow battery.
Citation Information
Patent Citations
Bipolar plate with reaction electrode layer for secondary battery
JP1994290796A
Carbon felt dipole plate and its forming method
JP1999162496A
Separator for fuel cell
JP2016119181A
Bipolar plate for redox flow battery and manufacturing method thereof
JP2019160795A
Bipolar plate for redox flow cell and manufacturing method thereof
JP2020068091A